Visualization of the peripheral vascularity by time-resolved computed tomography: a case report. (January 2019) - Svensson, Anders; Brismar, Torkel B
Runoff computed tomography angiography (CTA) is commonly used to diagnose peripheral artery disease (PAD) of the lower extremities. However, the risk of non-conclusive examination due to suboptimal timing and overrunning the contrast medium bolus is a major pitfall that must be considered. Here we describe two case studies using dynamic time-resolved CTA imaging of the peripheral vascularity.